Application of phenolic compounds as natural dye extracted from date-pits: dyeing studies of modified acrylic fibres. Issue 9 (3rd May 2019) - Dhahri, Hajera; Guesmi, Ahlem; Ben Hamadi, Naoufel
Abstract: This research work involves the dyeing of acrylic fabric with natural dye extracted from date pits powders using Soxhlet extraction process. The effect of dye bath pH, salt concentration, dyeing time and temperature were studied. The optimal dyeing conditions where pH 4, 0 g/L salt, 60 min, and 80 °C. The COD and the BOD5 of the residual dye bath were measured and it was shown from the registered values that the residual dye bath presents an acceptable rate of organic discharge. Abstract :